Calcification of the stylohyoid complex in Libyans - Galal Omami (Saudi Dental Journal)
Objective: To investigate the prevalence and pattern of calcification of the stylohyoid complex in Libyan population. Material and methods: Archived digital panoramic radiographs of 3343 patients were collected; 181 images were excluded for underage or poor image quality. Thus, the images of 3162 patients (1081 men, 2081 women; women-to-men ratio, 2:1; age range, 16–68 years; mean age, 36.7 years) retrieved and assigned to one of four morphological patterns of the stylohyoid complex: regular, elongated, calcified, and undetected. Data were analyzed with the Χ2 test using SPSS (Chicago, IL, USA); P values lower than 0.05 were considered statistically significant. Results: Out of 3162 images studied, the styloid process was demonstrated to be regular in 1935 (61.2%), elongated in 541 (17.2%), calcified in 565 (17.8%), and undetected in 121 (3.8%). Symmetric patterns were demonstrated on 2580 (81.6%) images. An elongated stylohyoid complex was significantly more common in women than in men (P = .0404). Conclusion: The anatomical patterns of the stylohyoid complex in Libyans were highly variable. Dental clinicians should recognize the various morphological patterns of the stylohyoid complex on panoramic radiographs. Computed tomography studies are recommended for further morphometric analysis of the stylohyoid complex. Keywords: Calcification, Radiography, Panoramic, Stylohyoid